Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1248/bpb.30.2126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginsenosides, Active Ingredients of Panax ginseng, on Development, Growth, and Life Span of Caenorhabditis elegans

Abstract: Ginseng, the root of Panax ginseng C. A. MEYER, has been used as a representative tonic for two thousand years in the Far East countries like Korea, China, and Japan. Now, ginseng is one of the most famous and precious herbal medicines consumed around the world. 1) Although ginseng exhibits multiple pharmacological actions in vitro or in vivo studies, its mechanisms on various efficacies are still elusive. Recent accumulating evidences show that ginseng saponins (or ginsenosides) are the main active ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Triterpene saponins are the principal bioactive constituents of the root of P. ginseng, which have been reported to show antitumor, antistress, antiaging, radioresistance, and immunostimulating activities, etc. [2][3][4][5][6][7][8][9]. Our previous phytochemical studies on the stems and leaves of P. ginseng had resulted in the isolation of four new and two known ginsenoside [10], and further chemical analysis had led to the isolation of three new dammarane-type triterpene saponins named ginsenosides Rh 18 (1), Rh 19 (3) and Rh 20 (4), along with two new triterpene sapogenins 12β,23(R)-epoxydammara-24-ene-3β,6α,20(S)-triol (2) and dammara-(20E)22,25-diene-3β,6α,12β,24S-tetrol (5).…”
Section: Introductionmentioning
confidence: 99%
“…Triterpene saponins are the principal bioactive constituents of the root of P. ginseng, which have been reported to show antitumor, antistress, antiaging, radioresistance, and immunostimulating activities, etc. [2][3][4][5][6][7][8][9]. Our previous phytochemical studies on the stems and leaves of P. ginseng had resulted in the isolation of four new and two known ginsenoside [10], and further chemical analysis had led to the isolation of three new dammarane-type triterpene saponins named ginsenosides Rh 18 (1), Rh 19 (3) and Rh 20 (4), along with two new triterpene sapogenins 12β,23(R)-epoxydammara-24-ene-3β,6α,20(S)-triol (2) and dammara-(20E)22,25-diene-3β,6α,12β,24S-tetrol (5).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous report, we could demonstrate that ginsenoside Rb 1 and Rc but not Rg 1 restored the average brood size, growth rate, percent development, and life span of C. elegans in cholesterol-deprived medium [6]. These results show a possibility that ginsenosides differentially affect development and growth of worm in cholesterol-deprived medium.…”
Section: Discussionmentioning
confidence: 52%
“…In the previous report, we have shown that supplements of ginseng total saponins (GTS) fraction and ginsenoside Rb 1 and Rc restored normal growth of C. elegans grown in cholesterol-deprived-medium [6]. These results show a possibility that the individual ginsenosides might have differential effects on growth of C. elegans .…”
Section: Introductionmentioning
confidence: 67%
“…Ginsenosides have been found to extend life span in a nematode model. 23 In a model of cellular senescence, the ginsenoside Rg1 has been found to increase telomerase expression and prevent terminal restriction fragment shortening (terminal restriction fragment analysis is considered the gold standard assay for measuring telomere length). 24 In a mouse model of hematopoietic stem cell aging, Rg1 was also determined to reduce the number of cells entering the G1 phase, decrease telomere shortening, and increase telomerase activity.…”
Section: Cistanche Genus Plantsmentioning
confidence: 99%